2004
DOI: 10.1037/0012-1649.40.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Child Personality and Parental Behavior as Moderators of Problem Behavior: Variable- and Person-Centered Approaches.

Abstract: Parenting ϫ Child Personality interactions in predicting child externalizing and internalizing behavior were investigated in a variable-centered study and a person-centered study. The variable-centered study used data from a 3-year longitudinal study of 600 children 7 to 15 years old at Time 1 and 512 children 10 to 18 years old at Time 2. Parents rated child personality (five factor model), negative control, positive parenting, and child problem behavior, whereas children rated parental behavior. Hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
149
4
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(175 citation statements)
references
References 82 publications
(122 reference statements)
17
149
4
5
Order By: Relevance
“…Results showed no association of maladaptive personality traits with anxiety. Taken together, results in children with MID are similar to results of studies in a normal population in that lower scores on Compulsivity (Prinzie et al, 2003;Van Leeuwen et al, 2004), higher scores on Emotional Instability (Tackett, 2006) and Disagreeableness (Prinzie et al, 2010) are risk factors for developing behavioral problems, supporting the vulnerability model. These maladaptive personality traits may function as a diathesis by predisposing a child with MID for developing behavioral problems under specific circumstances.…”
Section: Maladaptive Personality Traitssupporting
confidence: 80%
See 2 more Smart Citations
“…Results showed no association of maladaptive personality traits with anxiety. Taken together, results in children with MID are similar to results of studies in a normal population in that lower scores on Compulsivity (Prinzie et al, 2003;Van Leeuwen et al, 2004), higher scores on Emotional Instability (Tackett, 2006) and Disagreeableness (Prinzie et al, 2010) are risk factors for developing behavioral problems, supporting the vulnerability model. These maladaptive personality traits may function as a diathesis by predisposing a child with MID for developing behavioral problems under specific circumstances.…”
Section: Maladaptive Personality Traitssupporting
confidence: 80%
“…However, previous research has mainly focused on the associations between behavioral problems and measures of adaptive personality traits. For example, research in representative community samples has identified consistent relationships between low Conscientiousness, low Agreeableness, high Extraversion and to a lesser extent high Neuroticism (Prinzie et al, 2003;Prinzie, Van der Sluis, De Haan, & Deković , 2010;Tackett, 2006;Van Leeuwen, Mervielde, Braet, & Bosmans, 2004) and behavioral problems. Given the importance of personality in the forthcoming DSM-V (Widiger, 2011;Widiger & Mullins-Sweatt, 2009) and the fact that maladaptive personality traits have not yet been studied in children with MID, the third aim of this study was to investigate the association of behavioral problems with maladaptive personality traits.…”
Section: Maladaptive Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benevolence is conceptually and empirically related to the adult FFM domain of Agreeableness, whereas Imagination is associated with the Openness to Experience domain (De Fruyt et al, 2000). The HiPIC's robust factor structure and high internal consistencies of domains and facets have been documented in various studies with clinical and nonclinical samples (Van Hoecke, De Fruyt, De Clercq, Hoebeke, & Van de Walle, 2006;Van Leeuwen, De Fruyt, & Mervielde, 2004;Van Leeuwen, Mervielde, Braet, & Bosmans, 2004;Vollrath & Landolt, 2005). Domain scale reliabilities for the representative population and twin and sibling samples ranged from .76 (Extraversion, Time 1; representative population sample) to .89 (Conscientiousness, Time 1; twin and sibling sample), and for the facet scales, from .77 (Self-Confidence, Time 2; representative population sample) to .91 (Intellect, Time 1; twin and sibling sample).…”
Section: Questionnairesmentioning
confidence: 99%
“…However, from an ecological perspective which posits the child as nested in a complex network of interconnected systems (Bronfenbrenner, 1986), multiple sources, other than parenting, may contribute to EPB. Accumulating evidence suggests that the family is a critical environment related to a broad range of important social and emotional behaviors and that environmental influences interact with children's personal attributes in the emergence of problematic behavior (Feinberg, Neiderhiser, Simmens, Reiss, & Hetherington, 2000;Van Leeuwen, Mervielde, Braet, & Bosmans, 2004). In this respect, some investigators are calling for including the siblings in the traditional parent-child dyadic approach (e.g., Boyle et al, 2004), whereas others encourage the combination of multiple risk factors associated with EBP in order to consider their respective-additive or multiplicative-contribution (e.g., Sameroff et al, 1997).…”
Section: Introductionmentioning
confidence: 99%